Sectarian Violence: A Sociological Analysis of Sukkur Division - Danial Ahmed; Dr Ahmed Ali Brohi; Dr Hamadullah Kakepoto (Social Science Review Archives, 2025)
Abstract Purpose: To determine the causes, consequences, and potential outcomes of conflict resolution, this study investigates the social elements of sectarian violence in the Sukkur Division district. The study makes use of sociology to explain how to strengthen neighborhood relationships and produce long-lasting peace. Design/Methodology/Approach: The Data were collected through a questionnaire from the victims of sectarian violence. A sample size of 460 was randomly selected. Using techniques of descriptive statistics, reliability, and regression analysis to find out the consequences behind sectarian violence. All methods were performed in the SPSS 30 version for the data analysis. Findings: The findings emphasize the need for socio-politically tailored policies. These measures may strengthen efforts to address sectarian conflict's root causes and promote lasting peace. The study shows that political, social, religious, and historical factors complicate sectarian conflict in the Sukkur Division. The division has gradually developed sectarian divisions, especially in recent decades while accommodating several religious congregations. Economic inequality, political manipulation, and religious extremism raise tensions. Violence has increased due to the state's failure to address inequality and its sometimes-sectarian involvement. Political and religious leaders exploiting these differences for power has made unity and reconciliation harder.